Imenovanje in položaj arbitrov po Ljubljanskih arbitražnih pravilih - Djinović, Marko (Javna uprava, 2016)
Public law entities (the Republic of Slovenia and municipalities) are frequently involved as parties to arbitration proceedings in disputes arising out of concession agreements and public-private partnerships. The aim of this article is to present to the public law entities as users of arbitration the characteristics of the process for the appointment of arbitrators under the Ljubljana Arbitration Rules (the criteria for selection of arbitrators, number of arbitrators, the appointment procedure, standards of impartiality and independence and the functions of arbitrators). Particular emphasis is placed on the division of roles of the parties, the arbitrators and the arbitral institution (the Ljubljana Arbitration Centre) in the appointment process. The autonomy of parties in selecting arbitrators is one of the fundamental advantages of arbitration, which on the other hand encompasses a great deal of responsibility of the parties. Efficient and fair resolution of disputes ultimately depends on the quality of the appointed arbitrators. When acting as parties to arbitration proceedings, public law entities can equally benefit from all the advantages of arbitration.
Keywords: arbitration; arbitration law; arbitrators; arbitraža; arbitražno pravo; arbitri; concession contract; javno-zasebno partnerstvo; koncesijska pogodb; Ljubljana Arbitration Centre; osebe javnega prava; public law entities; public-private partnership; Stalna arbitraža pri GZS